East of Eden Movie Still - Warner Bros.:::Creator::::::::::::
Cal Trask (James Dean) walks with his arm around neck of his brother Aron Trask (Richard Davalos), who holds Abra Bacon's (Julie Harris') hand. RESTRICTED USE